Risk factors, prevention, and therapy of intraluminal stent thrombosis in frozen elephant trunk prostheses—what we know so far - Helms, Florian; Schmack, Bastian; Weymann, Alexander; Poyanmehr, Reza; Martens, Andreas; Salman, Jawad; Zubarevich, Alina; Schmitto, Jan D.; Ruhparwar, Arjang; Popov, Aron-Frederik (Frontiers in Cardiovascular Medicine, 2024)
Intraluminal thrombus formation (ILT) is a recently discovered and highly clinically relevant complication after frozen elephant trunk implantation in cardiovascular surgery. In this phenomenon, a thrombus forms within the lumen of the stent graft component of the frozen elephant trunk prosthesis and puts the patient at risk for downstream embolization with visceral or lower limb ischemia. Incidence of ILT reported in the currently available studies ranges from 6% to 17% of patients after frozen elephant trunk implantation. Adverse thromboembolic events include acute occlusion of the celiac and superior mesenteric arteries, both renal arteries as well as acute lower limb ischemia due to iliac or femoral artery embolization that not infrequently require interventional or open embolectomy. Therefore, the presence of ILT is associated with increased short-term mortality and morbidity. Currently proposed strategies to avoid ILT formation include a more aggressive anticoagulation management, minimization of postoperative coagulation factor application, and even technical optimizations of the stent graft portion itself. If ILT is manifested, the therapeutic strategies tested to date are long-term escalation of anticoagulation and early endovascular extension of the FET stent graft with overstenting of the intraluminal thrombus. The long-term efficiency of these prophylactic and therapeutic measures has yet to be proven. Nonetheless, all surgeons performing the frozen elephant trunk procedure must be aware of the risk of ILT formation to facilitate a timely diagnosis and therapy.